Restorative Justice Model in the Resolution of Criminal Acts Based on Customary Law and Local Culture - Marzuki, Ismail; Bulqis, Malikal; Putri, Dita Dwi Angela; Nadayah, Natasatun (Rechtsvinding, 2025)
The customary-based restorative justice model is an alternative to criminal justice that emphasizes the restoration of social relations, community involvement, and respect for local wisdom. Amidst the inefficiency of the national criminal justice system, that is often repressive, customary resolution mechanisms that exist in communities such as Baduy, Dayak, and Kei demonstrate principles of restorative justice that are similar to the international concept as formulated by Howard Zehr and the principles of the United Nations. This study aims to formulate an ideal model of customary-based criminal justice, while also examining its potential contribution to the reform of the national legal system. The method used is descriptive-analytical by a normative juridical approach, combining literature study, customary law review, and theoretical analysis of the principles of restorative justice. The results of the study show that there is substantial similarity among customary law and modern restorative justice, such as deliberative consensus, acknowledgment of wrongdoing, and restoration of victims' losses. However, the integration of customary models into the national legal system faces serious challenges, including disparities among communities, the risk of human rights violations, and resistance by formal legal institutions. Therefore, the ideal model formulated includes the principle of justice, deliberation-based procedural stages, classification of cases that can be resolved through customary law, and normative oversight mechanisms to ensure accountability. The conclusion of this study confirms that the application of customary models can handle the reform of the national criminal justice system by reducing the caseload, increasing community participation, and preserving local legal culture. The main recommendation is the need for national regulations that accommodate legal pluralism in a fair and contextual manner.